STRATEGI KOMUNIKASI PROGRAM TANAM JAJAR LEGOWO KEPADA MASYARAKAT PETANI PADI - Nuzuwir Joni; Asmawi Asmawi; Ernita Arif (Universitas Andalas, 2019)
System of Legowo row planting technology is innovation in agriculture which is highly recommended by the government in an effort to increase rice production in Indonesia. To accelerate the adoption of these technologies, it is necessary to prepare the right communication strategy. This study aims to determine the communication strategy of the Jajar Legowo planting program to the rice farming community in Padang City. This type of research is qualitative. Research data is obtained through in-depth interviews, participatory observation, and documentation. The data is processed by Miles and Huberman's interactive analysis model and the validity of the data by triangulation. The results showed that the communication strategy of legowo planting program was: (1) getting to know the target audience, namely rice farmers; (2) compile messages, in the form of benefits and procedures for implementing the program; (3) establish methods, in the form of: persuasion, educative, informative, and redundancy methods, (4) media use, in the form of discussions, lectures, brochures, leaflets, and banners. In addition, people's habits such as gathering and sitting in the store can be used as a place to introduce new technology. .